2016
DOI: 10.1016/j.prevetmed.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to Bovine viral diarrhoea virus 1 on risk of bovine respiratory disease in Australian feedlot cattle

Abstract: Viruses play a key role in the complex aetiology of bovine respiratory disease (BRD). Bovine viral diarrhoea virus 1 (BVDV-1) is widespread in Australia and has been shown to contribute to BRD occurrence. As part of a prospective longitudinal study on BRD, effects of exposure to BVDV-1 on risk of BRD in Australian feedlot cattle were investigated. A total of 35,160 animals were enrolled at induction (when animals were identified and characteristics recorded), held in feedlot pens with other cattle (cohorts) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
2
19
0
3
Order By: Relevance
“…The Australian National Bovine Respiratory Disease Initiative was a prospective longitudinal study in cattle in medium-sized to large Australian feedlot cattle that identified and quantified the effects of numerous putative risk factors for BRD (Hay et al, 2014;Hay et al, 2016a;Hay et al, 2016b;Hay et al, 2016c;Hay et al, 2016d;Hay et al, 2016e). The current study extends these findings.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The Australian National Bovine Respiratory Disease Initiative was a prospective longitudinal study in cattle in medium-sized to large Australian feedlot cattle that identified and quantified the effects of numerous putative risk factors for BRD (Hay et al, 2014;Hay et al, 2016a;Hay et al, 2016b;Hay et al, 2016c;Hay et al, 2016d;Hay et al, 2016e). The current study extends these findings.…”
Section: Introductionsupporting
confidence: 56%
“…These collapsed variables were used in the current study to simplify analyses and to ensure there were at least modest numbers of animals in each category. Exposure to 'BVDV in the cohort' (yes, no) was a cohort-level variable which categorised cohorts as exposed if any animal(s) had tested positive to Bovine viral diarrhoea virus 1 (BVDV-1) on qPCR testing (Hay et al, 2016a). The number of study animals in the animal's group-13 ('group-13N') essentially reflected the size of the animal's group of cattle over an extended period as the majority of group-13s had been stable (i.e.…”
Section: Study Design Study Population and Exposure Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Os Estados Unidos da América estimam uma perda anual com a afecção de aproximadamente U$ 1 bilhão, devido à queda produtiva, aumento de despesas com manejo, custos com medicamentos e morte dos animais (Hay et al, 2016a).…”
Section: Complexo Respiratório Bovino: Crbunclassified
“…O papel da BVD (Bovine Viral Diarrhea) na patogênese do CRB é certo como doença primária e pode facilitar a colonização de agentes patogênicos nos pulmões, cuja maior exposição ao vírus demonstra maior risco da infecção no complexo respiratório em confinamentos (Hay et al, 2016a). Hay et al (2016b) demonstraram em um estudo que animais não vacinados para BVD têm o risco de desenvolver problemas respiratórios multifatoriais aumentados.…”
Section: Vírus Da Diarreia Viral Bovinaunclassified